Rickets among a Group of Preterm Babies under the Age of Two Years at AL Ramadi Teaching Hospital for Maternity and Childhood - Mohammed Maher Al-Ani; Rana F. Shitran; Rafi Khaleel Al-Ani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Rickets of prematurity is a familiar status that leads to pathological fractures. Deficiency ofminerals leading to disturbed formation of bone is the most popular factor giving rise to disease and preterminfants are at increased risk of developing this condition.Objectives; To identify the incidence of rickets in preterm babies, and studying the risk factor associatedwith this disease like age, gender, residence, type of feeding, and changes in some biochemical tests.Patients and Methods: Across sectional study done in an outpatient clinic in maternity and childhoodteaching hospital, cases included in this study were children below two years old and were delivered before 37weeks of gestation. The diagnosis of rickets was done radiologically. All studied babies, data were collectedby history about (gender, age, type of feeding, and residence). Cases which diagnosed radiologically asrickets, a serological test was done for (serum calcium, phosphorus, alkaline phosphatase, and vitamin D).Results: (29.3%) of preterm babies were diagnosed as rickets of prematurity. The most common age reportedwith rickets was from 3months to less than13 months. Un-supplemented breast milk feeding was reported asa significant risk factor while residence and gender variation were not. High alkaline phosphatase level wasreported in more than (90%) of rickety children.Conclusion: A high incidence of rickets was found in preterm babies. Un-supplemented breastfeeding is animportant risk factor for the disease. Alkaline phosphatase activity and radiological features are importantfor screening.